RELIGIOUS COMMODIFICATION: THE PERFORMANCE OF ‘USTĀDHA HALIMAH AL-ALAYDRUS’ ON DAKWAH STAGE IN TARGETING INDONESIAN AUDIENCES - Harahap, Mariati Aprilia (Proceeding International Seminar of Islamic Studies, 2024)
This study explains the religious commodification aspect that has attracted many female audiences in Indonesia. Female preachers such as Sharīfa Halimah have commodified religion into more attractive and persuasive products. This paper analyzes factors that led her to become an influential preacher among her female listeners—born genealogically related to the Prophet Muhammad and her pious ancestors, having good rhetorical skills in persuading the audiences, and inheriting the magnet of Tarim have led her to become an influential Muslima saint figure in Indonesia. The use of relevant infrastructures supporting her callings to Islam, such as Instagram and YouTube channels, tends to be viral among young Indonesians. All these social media have become practical tools to spread the messages of Islam among Indonesians, especially the female youth generations. This study uses qualitative research analysis, including participatory observation, textual analysis, and interviews, to support the remark. Some secondary data was also acquired from her writing books and recorded videos from YouTube and Instagram channels. The result found that her blood relationship with the Prophet, the way she talks in a moderate, polite, and persuasive manner, and a graduate of Tarim school have led her to become an influential, famous preacher in Indonesia.